2020
DOI: 10.1111/eip.12984
|View full text |Cite
|
Sign up to set email alerts
|

Community stakeholders' perspectives on youth mental health in India: Problems, challenges and recommendations

Abstract: Background: India has a large youth population whose mental health needs must be addressed. This includes promotion of positive mental health, with early detection and effective intervention for mental health disorders. Understanding the perspectives of community stakeholders working with youth is pivotal to this effort. Current study aimed to bring together a group of community stakeholders (eg, parents, teachers, policy makers) to understand their perspectives on youth mental health problems, challenges in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Teachers' personal charm is one of the main external factors of students' academic emotions also embodies the teachers' mental health is the main harm of students' academic emotional development have active personal psychological quality teachers can with the help of its cheerful and open emotion feeling pure students, make the students in the learning education activities and homework experience happy, peaceful active academic emotions [11]. Emotion is closely related to the development of 3 Journal of Environmental and Public Health cognitive ability processing level, which can arouse the learning potential of students 'curriculum and promote the development of students' creativity and independent innovation ability.…”
Section: Impact On Students' Academic Development Thementioning
confidence: 99%
“…Teachers' personal charm is one of the main external factors of students' academic emotions also embodies the teachers' mental health is the main harm of students' academic emotional development have active personal psychological quality teachers can with the help of its cheerful and open emotion feeling pure students, make the students in the learning education activities and homework experience happy, peaceful active academic emotions [11]. Emotion is closely related to the development of 3 Journal of Environmental and Public Health cognitive ability processing level, which can arouse the learning potential of students 'curriculum and promote the development of students' creativity and independent innovation ability.…”
Section: Impact On Students' Academic Development Thementioning
confidence: 99%
“…Notably, updating the systematic review also highlighted several studies that contribute to the social context of mental-health-related stigma. A qualitative study of community stakeholder perspectives (not including youth) described that schools are hesitant to acknowledge the extent of mental health problems and students fear being labelled, thereby creating an environment of hiding mental health problems [100]. The study also highlighted the need for school and college counsellors and mental health training for teachers.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“… 28 Another study concluded that social media use is a common driver of mental health issues among youth in India. 29 A study from Cape Town, South Africa found associations between social media use and both sleep difficulties and depressive symptoms. 30 Studies from Iran observed that individuals who did not use social networks like Instagram and Facebook had significantly lower levels of anxiety and depression 31 and that social media use by adolescents was correlated with lower life satisfaction as well as lower family social capital.…”
Section: Benefits and Harms Of Social Mediamentioning
confidence: 99%